Understanding Toxicity in Online Gaming: A Focus on Communication-Based Behaviours towards Female Players in Valorant - Anissa Maharani; Virienia Puspita; Raden Arny Aurora; Nico Wiranito (Jurnal Syntax Admiration, 2024)
Online multiplayer video games have emerged as a significant social platform, especially during the Covid-19 pandemic, offering solace and community for many individuals, particularly young people. However, alongside the benefits, online gaming environments have also become breeding grounds for toxic behaviours, disproportionately affecting minority groups within the gaming community, such as women. This study explores toxic behaviours within the competitive gaming environment of Valorant, focusing on communication-based toxicity experienced by female players. Through participative observation and analysis of game recordings, the study identifies various forms of toxicity, including verbal abuse, gender-based harassment, and sexual innuendos. Findings reveal a reluctance among female players to use voice communication due to fear of harassment, perpetuating gender stereotypes and marginalising women within the gaming community. Moreover, the phenomenon of smurfing exacerbates issues within the community, contributing to heightened frustration and hostility, particularly towards minority players. Addressing toxic behaviours in online gaming requires a comprehensive approach involving game developers, community initiatives, and education efforts to promote inclusivity and respect. By fostering a culture of mutual respect, the gaming community can create a safer and more welcoming environment for all players.